Pembuatan Produk Permen Agar-agar Buah - Rahayu, Mamik Ponco; Harmastuti, Nuraini; Rejeki, Endang Sri; Turahman, Taufik (LPPM UNS, 2019)
ABSTRACT The Ngampon people in Mojosongo Village, Jebres, Surakarta City face diverse livelihood problems, most of which are factory workers with low income levels and the role of mothers as housewives. Therefore, it is necessary to have training activities to make agar agar fruit products as an alternative home-based home industry to increase family income. This community service activity was designed by conducting training on making fruit jelly candy products. The target of the above activities is that the community will get additional skills in making agar-agar candy fruit that can be done easily and small capital so that it can be an alternative family home industry. Keywords: Fruit, jelly candy, home industry